The Impact of E-CRM and Customer Experience on E-Commerce Consumer Loyalty Through Satisfaction in Indonesia - Nurjannah Nurjannah; Erwina Erwina; Jafar Basalamah; Muh. Haerdiansyah Syahnur (Universitas Mercu Buana, 2022)
Objectives: The objective of this research is to examine how the relationship between E-CRM and customer experience affects customer loyalty through customer satisfaction. Internet use grows year after year, especially in Indonesia. New terms emerge to describe the increase in internet use or utilization in our daily lives, such as IoT (internet of things), AI (artificial intelligence), startups, and Big Data, among others. As a result of technological advancements, most notably the use of the internet, the industrial world is also advancing at a fast pace.Methodology: The online questionnaire was randomly distributed to people who had used e-commerce at least once during the pandemic (march 2020 - now). The sample consisted of 85 people who were selected by purposive sampling technique and analyzed using the PLS 3 SEM application.Finding: Customer experience did not affect customer satisfaction, and also customer experience did not affect customer loyalty through customer satisfaction. Meanwhile, customer satisfaction assisted effect E-CRM on customer loyalty. Customer satisfaction affects customer loyalty.Conclusion: The study's findings should assist in the advancement of science, particularly in the fields of digital marketing and consumer behaviour. It is also expected to provide feedback to e-commerce industry participants in order to assist them in improving their customer experience in order to maintain customer satisfaction and consumer loyalty.